Long term experiment confirms blue fox's good tolerance of formic acid treated feed - Pölönen, Ilpo; Koskinen, Nita; Sepponen, Juhani; Rekilä, Teppo (dk, 2007)
Regardless of several years of extensive, controlled use of formic acid in fur animal feed in Finland, without any confirmed negative effects on animal health or performance, there still exist viewpoints that doubt suitability of formic acid for fur animals. For example, formic acid has been combined with rather low breeding result of Finnish blue foxes. The purpose of this experiment was to test those doubts. Therefore, incremental levels of formic acid, from 0 to 1,2% in feed were tested for long term effects in blue foxes. The highest level of formic acid, 1,2 %, was 50 % higher than currently recommended maximum levels. Additionally, FurmixTM concept (combination of preservatives with sulphuric acid) was tested at one level (1,4 % w/w) as well. The experiment started with weaned blue fox females and lasted for two breeding seasons till weaning. All the experimental animals, four groups, 49 females in each group continued for the second year, regardless of breeding success in the first year. Experimental feeds or slaughterhouse by-products were not exposed to spoilage pressure prior to feed manufacturing or feeding. The acids were mixed in the feed, except FurmixTM that was first applied into slaughterhouse by-products, shortly before mixing into diet. Animals were fed restrictively to avoid obesity at mating. Overall results of the experiment were very good. Animals were healthy and the cubs grow well in all feeding groups. Breeding results, counted seven weeks after parturition per inseminated female, ranged from 4,3 - 5,0 in the first parturition and from 7,2 - 8,7 in the second. There were no statistical differences between feeding groups in breeding results, insemination or whelping dates. The results of the experiment confirm that blue foxes tolerate formic acid well, and the acid does not disturb development of puberty or reproductive physiology. Furthermore, FurmixTM together with sulphuric acid proved not to have negative effects either. It can be concluded, that the currently recommended maximum formic acid concentrations in blue fox feed in Finland, 0,3-0,4 % during breeding, pregnancy, lactation and early growth periods, and 0,8 % from September till pelting, do not jeopardize breeding results of blue foxes.
Keywords: Ko; sinikettu; turkiseläimet; rehut; muurahaishappo; furbearing animals; feeds; formic acid; tolerance; blue fox; fur animals; toleranssit